Effects of hopeaphenol and malibatol a isolated from bark of Hopea odorata Roxb on membrane enzymes and glycolysis of Streptococcus mutans - Huy, Nguyen Quang; Nghia, Phan Tuan (Academia Journal of Biology, 2014)
Hopeaphenol and malibatol A isolated from the bark of Hopea odorata Roxb were found to have a multitarget effect for the dental caries pathogen Streptococcus mutans. Hopeaphenol and malibatol A at a concentration of 4 mM inhibited acid production by Streptococcus mutans GS-5 in a pH-drop assay with excess glucose. Both the compounds at milimolar concentrations were also found to be highly lethal for S. mutans GS-5 and their lethal effect at pH 4 was stronger than that at pH 7. Our further studies indicated that hopeaphenol and malibatol A in the same range of concentrations inhibited the activity of membrane enzymes (F-ATPase, phosphoenol pyruvate: phosphotransferase system), glycolyic enzymes (pyruvate kinase, lactate dehydrogenase) and NADH oxidase of S. mutans. The obtained results suggested that the two compounds could have a potential use in oral care products.